Introduction to medical physics: Bridging physics and healthcare - Evelyn Pratami Sinaga; Rizki Budiman; M. Arif Nurdin; Josua T. Manik; E. H. Hasdeo (Nur Science Institute, 2026)
Medical physics is a rapidly developing field, with increasing demand for qualified professionals in Indonesia following regulations requiring hospitals to employ medical physicists. This community service program was conducted to introduce high school students to the applications of physics in healthcare and to improve their understanding and perception of physics as an applied and career-relevant discipline. The activity was carried out in collaboration between Matana University and SMA Stella Maris BSD, featuring interactive scientific talks and expert discussions on medical imaging, radiation therapy, and emerging topics in medical physics. Participants were 11th-grade science-track students, and program effectiveness was evaluated using pre-test and post-test assessments. The results showed a clear improvement in students’ understanding of physics applications in healthcare, with average scores increasing from 83.2 to 92.8, representing an improvement of approximately 11.5%. Qualitative feedback further indicated increased student interest in physics and greater awareness of career opportunities in medical physics, biomedical engineering, and healthcare technology.